Biological, Molecular and Phiysiological Characterization of Four Soybean mosaic virus Isolates Present in Argentine Soybean Crops - Maugeri Suarez, Mariel; Rodriguez, Marianela; Bejerman, Nicolas Esteban; Laguna, Irma Graciela; Rodriguez Pardina, Patricia (BioRxiv, 2022)
Soybean mosaic virus (SMV) causes systemic infections in soybean plants, leading to chlorotic mosaic and producing significant yield losses. The virus is widely distributed in all soybean production areas in the world. In Argentina, three geographical isolates were identified: Marcos Juárez (MJ), Manfredi (M), and North Western Argentina (NOA), and another isolate named “Planta Vinosa” (PV), which causes severe necrosis symptoms in some cultivars. Here, the biological, molecular and physiological characterization of these isolates was performed for the first time. Three of the four isolates showed a low genetic divergence in the evaluated genes (P1, CI and CP). Although SMV-NOA and SMV-PV had high homology at the sequence level, they showed wide differences in pathogenicity, seed mottling and the ability of transmission by seeds or aphids, as well as in physiological effects. SMV-NOA caused early alterations (before symptom appearance, BS) in ΦPSII and MDA content in leaves with respect to the other isolates. After the appearance of macroscopic symptoms (late symptoms, LS), SMV-M caused a significant increase in the content of MDA, total soluble sugars, and starch with respect to the other isolates. Thus, early alterations of ΦPSII and soluble sugars might have an impact on late viral symptoms. Likewise, SMV-MJ developed more severe symptoms in the susceptible Davis cultivar than in DM 4800. Therefore, our results show differences in genome, biological properties and physiological effects among SMV isolates as well as different interactions of SMV-MJ with two soybean cultivars.